Sustainable Malls with Green Outdoor: Enhancing Shopping Experience and E-WoM Activity - Pangihutan, Windrapraja; Wibowo, Mas Wahyu (Journal of Sustainable Economic and Business, 2025)
Objectives: This study examines the influence of shopping value on e-WoM activity intention, with self-congruity and shopping well-being as mediating variables, within the context of shopping malls featuring green open spaces in Indonesia.Methodology: A quantitative research design was employed, utilizing data collected from 199 respondents through a 7-point Likert scale questionnaire. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the Disjoint Two-Stage Approach, which distinguishes between lower-order and higher-order components to ensure robust statistical analysis.Findings: The results indicate that shopping value has a significant positive effect on self-congruity and shopping well-being; however, its direct effect on e-WoM activity intention is not supported. Furthermore, shopping well-being exhibits a significant mediating effect in this relationship, whereas self-congruity does not demonstrate statistical significance as a mediator.Conclusion: These findings highlight the critical role of consumer emotional well-being in fostering e-WoM activity. The study provides valuable managerial insights, emphasizing the importance of sustainable green spaces in enhancing consumer engagement and enriching the shopping experience.